Effect of laser power on the formation of porous graphitic carbon on polyimide film - Soaid, N.I. (Institute of Electrical and Electronics Engineers Inc., 2019)
Polymer based materials can be used as conductive film for various application. Incorporation of fragile materials with polymer may enhance the flexibility of the materials itself. Here, graphitic carbon has been developed using a single-step process using laser scriber. This study used different percentage () of laser power during the laser scribing process. Surface morphology analysis indicates the porosity of graphitic carbon decrease with the increment of laser power due to the high thermal energy from the laser. In addition, oxygen content also increased due to graphitic carbon layer itself absorb oxygen from the atmosphere where partial oxidation take place during the laser scribing process. Raman spectrum shows the existence of graphitic band (G-band) around ~1580 cm-1, possible presence of graphene layers with high defects. Â© 2019 IEEE.